Aluminum nitride powder and polymer molding
Patent Information
- Application Number
- JP2024206932
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-26
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure 2025027053000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an aluminum nitride powder. [Background technology]
[0002] Taking advantage of its excellent thermal conductivity, aluminum nitride powder is used as a filler to be mixed into materials such as resins, greases, adhesives, paints, etc. The material properties required for a filler include packing ability, kneadability, and thermal conductivity, and various efforts are being made to improve the material properties.
[0003] Previously, in Patent Document 1, the applicant of the present application reported that by using spherical aluminum nitride powder with high sphericity, in which 70% or more of the particles have an outer periphery that does not contain sharp corners or unevenness, it is possible to improve filling properties, kneading properties, and thermal conductivity.
[0004] Furthermore, the applicant of the present application reported in Patent Document 2 that fluidity and filling properties can be improved by using spherical aluminum nitride powder having a median diameter (D50) of 1.9 to 4.0 μm, 10% or less of particles having a particle diameter of 0.9 μm or less, 10% or less of particles having a particle diameter of 7 μm or more, and a sphericity of 0.8 or more.
[0005] The spherical aluminum nitride powders of Patent Documents 1 and 2 are basically produced by adding and mixing a rare earth compound powder, a calcium compound powder, and a carbon powder to an aluminum nitride raw material powder, heat treating the mixture in a non-oxidizing atmosphere to promote the spheroidization and growth of the particles, and then heat treating the mixture in an oxidizing atmosphere to decarburize the particles.
[0006] Next, Patent Document 3 states the general theory that if coarse particles are contained in the filler, clogging will occur when filling gaps, resulting in uneven filling, voids, and molding defects, and that the presence of agglomerated particles can also cause deterioration of fluidity.Then, it states that no aluminum nitride powder has been reported in which the amount of coarse particles or agglomerated particles has been controlled, and reports an aluminum nitride powder that has been classified by removing excess coarse particles.
[0007] Regarding classification, Patent Document 3 states that various methods such as dry methods (sieve classification, air classification) and wet methods (wet filter classification, fluid classification) can be used, but air classification and wet classification are more efficient at removing coarse particles, and further states that wet classification leaves fewer coarse particles after classification than air classification, and that wet filter classification has better accuracy and higher productivity than fluid classification, and in the examples only wet filter classification is used. Wet filter classification is a classification method in which powder is dispersed in a solvent, deagglomerated, and then passed through a filter. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Patent No. 6700460 [Patent Document 2] Patent No. 7149379 [Patent Document 3] Patent No. 7017556 Summary of the Invention [Problem to be solved by the invention]
[0009] However, the aluminum nitride powders of Patent Documents 1 and 2, when produced by the above-mentioned methods, still have room for improvement in terms of wettability with polymeric materials such as resins.
[0010] The inventors of the present application suspected that subjecting aluminum nitride powder to wet classification as in Patent Document 3 might affect its wettability with polymeric materials such as resins, and conducted follow-up tests on the aluminum nitride powder in the examples of Patent Document 3. As a result, it was found that the wettability with polymeric materials such as resins was worse after classification than before classification (see the oil absorption amounts of Comparative Examples 2 and 4 described below).
[0011] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide an aluminum nitride powder having excellent wettability with polymeric materials such as resins. [Means for solving the problem]
[0012] The inventors further investigated whether it was possible to improve the wettability of aluminum nitride powder with polymeric materials such as resins by changing the particle surface state of the aluminum nitride powder. As a result, they found that it was possible to improve the wettability of aluminum nitride powder with polymeric materials such as resins by subjecting the aluminum nitride powder to a specified dry classification, and after further investigations they arrived at the present invention.
[0013] [1] Aluminum nitride powder having an oil absorption of 13.5g / 100g or less based on the refined linseed oil method in accordance with JIS K5101-13-1:2004.
[0014] The oil absorption based on the refined linseed oil method in accordance with JIS K5101-13-1:2004 (ISO 787-5:1980) is calculated by adding a small amount of silicone oil to 10g of powder, kneading it with a spatula, spreading it without breaking or crumbling, and dropping an amount that lightly adheres to the measuring plate, and converting it to the amount dropped per 100g of powder. The silicone oil used was KF96-300CS manufactured by Shin-Etsu Chemical Co., Ltd. The measured value of the oil absorption was calculated by taking the average value of 10 measurements. The smaller the oil absorption value, the better the wettability of the powder with oil, and the better the wettability with polymeric materials such as resins. It is more preferable that the oil absorption is less than 13.0 g / 100 g.
[0015] [2] The aluminum nitride powder according to the above [1], having a median diameter (D50) of 1.5 to 10 μm.
[0016] If the median diameter (D50) is less than 1.5 μm, agglomerated particles are likely to occur, making it difficult to use as a heat dissipating filler, whereas if the median diameter (D50) is more than 10 μm, it becomes difficult to form a thin layer of the polymer molded article.
[0017] [3] Aluminum nitride powder having a median diameter (D50) of 1.5 to 10 μm and a rising tangent angle on the small diameter side of a particle size distribution curve of 45° or more. [3'] Aluminum nitride powder having a (D90-D10) / D50 value of 1.11 or less and a rising tangent angle on the small diameter side of the particle size distribution curve of 45° or more.
[0018] The median diameter (D50) is as described above. The value of (D90-D10) / D50 is an index of the sharpness of the particle size distribution, as described later, and the smaller the value, the sharper the particle size distribution. The rising tangent angle on the small diameter side of the particle size distribution curve is the angle formed by the rising tangent and the x-axis (logarithmic axis of particle diameter), and is calculated using the procedure described below. If this rising tangent angle is 45° or more, the number of fine crushed particles is small, and thus the wettability with polymer materials such as resins is improved. This rising tangent angle is preferably 50° or more, and more preferably 55° or more.
[0019] [4] A polymer molded product obtained by filling a polymer material with the aluminum nitride powder according to any one of the above [1] to [3'].
[0020] [5] A method for modifying aluminum nitride powder, comprising classifying the aluminum nitride powder using a dry jet mill. [6] A method for modifying aluminum nitride powder, comprising classifying the aluminum nitride powder using a dry jet mill so that the oil absorption after classification based on the refined linseed oil method in accordance with JIS K5101-13-1:2004 is 89.5% or less of the amount before classification.
[0021] By classifying aluminum nitride powder using a dry jet mill, not only does the aggregated powder undergo disintegration / pulverization, resulting in a reduction in Dmax and a sharpening of the particle size distribution, but because the collection method for the dry jet mill is a cyclone, fine crushed particles are less likely to be included in the classified powder, and the oil absorption is reduced, improving the wettability with polymeric materials such as resins. Although wet classification allows for adjustment of particle size distribution equivalent to that achieved by dry jet mill classification, the oil absorption does not decrease. The reason why there is a difference in oil absorption despite the same particle size distribution is currently unknown, but it is thought that this is because the state of the particle surface newly exposed by crushing or pulverization using a dry jet mill is different from the state of the surface that was originally exposed. Effect of the Invention
[0022] According to the present invention, it is possible to provide an aluminum nitride powder having high wettability with polymeric materials such as resins. [Brief description of the drawings]
[0023] [Figure 1] 1A is a SEM photograph of the aluminum nitride powder of Example 1 at a magnification of 100 times, and FIG. 1B is a SEM photograph at a magnification of 2000 times. [Diagram 2] 2A is a SEM photograph of the aluminum nitride powder of Comparative Example 1 at a magnification of 100 times, and FIG. 2B is a SEM photograph of the aluminum nitride powder of Comparative Example 1 at a magnification of 2000 times. [Diagram 3] 3A and 3B are SEM photographs of the aluminum nitride powder of Comparative Example 2 at a magnification of 100 and 2000, respectively. [Figure 4] FIG. 4 is a graph showing particle size distribution curves of Examples 1, 2, and 3 and Comparative Examples 1 and 2 (A-02-F system), and FIG. 4b is an enlarged view of the rising edge of (a). [Diagram 5] FIG. 5 is a graph showing particle size distribution curves of Examples 4 and 5 and Comparative Examples 3 and 4 (A-05-F system), and FIG. 5b is an enlarged view of the rising edge of (a). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] <1> Aluminum Nitride Powder (A) Composition The composition of the aluminum nitride powder is not particularly limited, but may contain, in addition to aluminum nitride, a rare earth compound derived from the production method, and may further contain a calcium compound.
[0025] The rare earth compound is not particularly limited, but is preferably 3.0 mass% or less in terms of oxide relative to 100 mass% of aluminum nitride. If the rare earth compound exceeds 3.0 mass%, the purity of aluminum nitride decreases, and there is a concern that the thermal conductivity will decrease.
[0026] The rare earth compound is not particularly limited, but examples thereof include oxides or halides of Y, Yb, La, Nd, and Sm.
[0027] The calcium compound is not particularly limited, but is preferably 0.5 mass% or less in terms of oxide relative to 100 mass% of aluminum nitride. If the calcium compound exceeds 0.5 mass%, the purity of aluminum nitride decreases, and there is a concern that the thermal conductivity will decrease.
[0028] (a) Manufacturing method The aluminum nitride powder (before the dry jet mill treatment) is not particularly limited in its manufacturing method, and a commercially available product may be used. Examples of the manufacturing method include the manufacturing methods described in Patent Document 1 or Patent Document 2.
[0029] (c) Classification (modification method) using a dry jet mill In classification using a dry jet mill, gas is ejected from an ejection nozzle, the raw material particles are accelerated by the jet stream, and the particles are pulverized by collision and grinding. The dry jet mill device used for this is not particularly limited, and any publicly known or commercially available dry jet mill device can be used.
[0030] <2> Polymer molded body The aluminum nitride powder of the present invention can be used to prepare polymeric molded articles having high thermal conductivity by filling them into polymeric materials, such as resins, rubbers, elastomers, and the like.
[0031] <3> Purpose Applications of the aluminum nitride powder are not particularly limited, but examples include fillers to be mixed into materials such as polymer materials, greases, adhesives, and paints. Applications of the polymer molded article obtained by filling a polymer material with the aluminum nitride powder of the present invention as a filler are not particularly limited, and examples thereof include circuit boards used in semiconductor modules, LED packages, Peltier modules, printers, multifunction machines, semiconductor lasers, optical communications, high frequencies, etc., general-purpose heat dissipation members, heat dissipation members (heat sinks) for power semiconductor modules, insulating plates, etc. EXAMPLES
[0032] Next, examples embodying the present invention will be described with reference to the drawings, while comparing them with comparative examples. Note that the materials, quantities and conditions of each part in the examples are merely examples, and can be appropriately changed without departing from the gist of the invention.
[0033] As shown in Table 1, "A-02-F" manufactured by MARUWA Co., Ltd. (applicant of the present application) was used as the aluminum nitride powder starting material in Examples 1, 2, and 3 and Comparative Examples 1 and 2, and "A-05-F" manufactured by the same company was used in Examples 4 and 5 and Comparative Examples 3 and 4. Hereinafter, the term "each example" refers to each of Examples 1 to 5 and Comparative Examples 1 to 4.
[0034] [Table 1]
[0035] In Examples 1, 2, and 3, "A-02-F" was classified using a dry jet mill "PJM-80" manufactured by Nippon Pneumatic Mfg. Co., Ltd. The grinding pressure was 0.4 MPa in Example 1, 0.3 MPa in Example 2, and 0.2 MPa in Example 3. The raw material supply amount (processing amount) was 300 g / hr. The number of grinding passes was one pass. The atmosphere of the entire line was air. The collection method of the dry jet mill is a cyclone, so that particularly fine crushed particles are removed and are not included in the powder after classification.
[0036] In Comparative Example 1, "A-02-F" was used as is, and no classification was carried out.
[0037] In Comparative Example 2, "A-02-F" was dispersed in IPA and allowed to stand to allow the aggregated particles and coarse particles to settle, and the supernatant was then collected, filtered, and dried. The standing time was adjusted so that the D50 of Comparative Example 2 was close to the D50 of Examples 1, 2, and 3.
[0038] In Examples 4 and 5, "A-05-F" was classified using the dry jet mill "PJM-80" and the grinding pressure was 0.4 MPa in Example 4 and 0.3 MPa in Example 5. The raw material supply amount (processing amount) was 300 g / hr. The number of grinding passes was 1 pass. The atmosphere of the entire line was air. The collection method was a cyclone.
[0039] In Comparative Example 3, "A-05-F" was used as is, and no classification was carried out.
[0040] In Comparative Example 4, "A-05-F" was dispersed in IPA and allowed to stand to allow the aggregated particles and coarse particles to settle, and the supernatant was then collected, filtered, and dried. The standing time was adjusted so that the D50 of Comparative Example 4 was close to that of Examples 4 and 5.
[0041] The aluminum nitride powder obtained in each example was subjected to the following observations and measurements.
[0042] (1) SEM photo observation FIG. 1 is an SEM photograph of the aluminum nitride powder of Example 1, FIG. 2 is an SEM photograph of the aluminum nitride powder of Comparative Example 1, and FIG. 3 is an SEM photograph of the aluminum nitride powder of Comparative Example 2, where (a) is a magnification of 100 times and (b) is a magnification of 2000 times.
[0043] Compared with Comparative Examples 1 and 2, Example 1 has smaller variation in particle size of the aluminum nitride powder and fewer agglomerates.
[0044] (2) Particle size distribution 0.5 g of aluminum nitride powder from each example was added to 50 ml of 0.1 mass % aqueous sodium pyrophosphate solution and dispersed for 3 minutes at 80% output using a US-300E manufactured by Nippon Seiki Seisakusho Co., Ltd. The particle size distribution based on volume was measured using a laser diffraction particle size distribution measuring device, model SALD-2200, manufactured by Shimadzu Corporation. The measurement results are shown in Table 1, Figures 4 and 5. Dmax = D99.99.
[0045] Although "A-02-F" originally mainly contains 2 μm particles, the peak top of Comparative Example 1 is at 3 to 4 μm, as shown in the particle size distribution in Figure 4(a). This is due to some of the 2 μm particles being aggregated. The peak top shifted to about 3 μm in Comparative Example 2 because agglomerated particles and coarse particles were removed by wet classification. The peak top shifted to 2-3 μm in Examples 1-3 because agglomerated particles were disintegrated by a dry jet mill. However, the peak top did not reach 2 μm or less in any of the examples, probably because no or little crushing of 2 μm particles occurred.
[0046] Although "A-05-F" originally mainly contains 4 μm particles, the peak top of Comparative Example 3 is at 5.5 to 6 μm, as shown in the particle size distribution in Figure 5(a). This is due to some of the 4 μm particles agglomerating. The peak top shifted to 4-5 μm in Comparative Example 4 because agglomerated particles and coarse particles were removed by wet classification, and the peak top shifted to about 4 μm in Examples 4 and 5 because agglomerated particles were disintegrated by the dry jet mill.
[0047] (3)(D90-D10) / D50 The calculation results of (D90-D10) / D50 are shown in Table 1. This value is an index of the sharpness of the particle size distribution, and the smaller the value, the sharper the particle size distribution.
[0048] Compared to Comparative Example 1, Comparative Example 2 and Examples 1 to 3 clearly had smaller values. Compared to Comparative Example 3, Comparative Example 4 and Examples 4 and 5 have clearly smaller values.
[0049] (4) Rising tangent angle on the small diameter side The rising tangent angle on the small diameter side of the particle size distribution curve is the angle formed by the rising tangent shown in Figure 4 (b) and Figure 5 (b) and the x-axis (logarithmic axis of particle diameter), and was calculated by the following procedure. i) Read two plotted points on the small diameter side of the particle size distribution curve and designate them as (x1, y1) and (x2, y2). Here, x is the particle diameter, y is the relative particle amount, and y1=0. Let x2 be any point in the range where logx2-logx1 satisfies 0.040-0.050. In Figure 4(b) and Figure 5(b), the second point (x2, y2) that was actually read is indicated by an arrow. ii) If the line connecting the two points is considered to be a tangent to the particle size distribution curve, the slope of the tangent is y2 / (x2-x1). iii) tan -1 and calculate the angle of the tangent. The calculation results are shown in Table 1.
[0050] Compared to Comparative Example 1, the increase in the tangent angle in Comparative Example 2 is slight, but the increase in the tangent angle in Examples 1 to 3 is very large. Compared to Comparative Example 3, the increase in the tangent angle in Comparative Example 4 is slight, but the increases in the tangent angle in Examples 4 and 5 are very large. The results of Examples 1 to 5 show that, since the collection method of the dry jet mill is a cyclone as described above, particularly fine crushed particles are removed and are not included in the powder after classification.
[0051] (5) Oil absorption amount The oil absorption was measured based on the refined linseed oil method in accordance with JIS K5101-13-1:2004.
[0052] Compared to Comparative Example 1, Comparative Example 2 had a large oil absorption amount, while Examples 1 to 3 had small oil absorption amounts. Compared to Comparative Example 3, Comparative Example 4 had a large oil absorption amount, but Examples 4 and 5 had small oil absorption amounts. As mentioned above, the results of Examples 1 to 5 are unclear at present, but it is believed that the surface state of the particles newly exposed by crushing or pulverizing with a dry jet mill is different from the surface state originally exposed. Thus, by using aluminum nitride powder with an oil absorption of 9.0g / 100g to 13.5g / 100g based on the refined linseed oil method according to JIS K5101-13-1:2004 as a filler in polymer materials such as resins, the wettability is good and the kneadability is improved.
[0053] The present invention is not limited to the above-described embodiment, and can be embodied by making appropriate modifications without departing from the gist of the invention.
Claims
1. An aluminum nitride powder having a (D90-D10) / D50 value of 1.11 or less and a rising tangent angle on the small diameter side of a particle size distribution curve of 45° or more.
2. A polymer molded product comprising a polymer material filled with the aluminum nitride powder according to claim 1.
Citation Information
Patent Citations
Production of aluminum nitride powder
JP1989096004A
Aluminum nitride powder
JP2014080362A
Composite powder material for flame spray and flame sprayed insulation base plate
JP2016074935A
Spherical aluminum nitride powder
JP2020023435A
Aluminum nitride powder and method of producing same
WO2021161883A1